115P Therapeutic efficacy of combining the tumour checkpoint controller BAL101553 (lisavanbulin) and immunomodulation in two mouse glioma models with different immunological status. (15th December 2019) - Genoud, V; Marinari, E; Bes, V; Dietrich, P-Y; McSheehy, P; Bachmann, F; Lane, H; Walker, P R
Abstract: Background: Glioblastoma (GBM) is a highly malignant brain tumour with no curative treatments. Immunotherapies, including immune checkpoint inhibitors (ICI) are under clinical evaluation, but have not yet been proven to have major impact. The low immune infiltration and modest mutational load of most GBM suggest that combination therapies will be required to improve sensitivity to immunotherapies. Methods: Two mouse GBM models were used, the immunogenic GL261 and the stringent, less mutated SB28. A novel, brain-penetrant, microtubule-targeting agent, BAL101553 (BAL) which induces tumour cell death through activation of the spindle assembly checkpoint, and an agonistic anti-CD40 antibody were combined with ICI (antibodies targeting PD-1 and CTLA-4) to evaluate potential therapeutic synergy. Tumours were analyzed molecularly (mutations, transcriptional profiling) and immunologically (immune infiltration, therapy response in T/B-cell deficient mice). Results: Well-tolerated combination therapies that significantly enhanced survival were identified in both SB28 and GL261 GBM models. The aggressive SB28, most representative of untreated human GBM, was most responsive to BAL combined with anti-CD40 (median survival in days: vehicle=27, anti-CD40=29, BAL=42, BAL/CD40=49); this effect was found to be T-cell independent as a similar result was observed in SB28 glioma-bearing immunodeficient (RAG1 KO) mice. The immunogenic GL261 model was, as predicted, responsive to ICI; it was relatively insensitive to BAL and anti-CD40 monotherapies but responsive to a combination of these two treatments (median survival in days: vehicle=28, anti-CD40=30, BAL=33, BAL/CD40=40). Conclusion: Combination GBM therapies that include immunomodulation will likely require selection of patients according to immunological characteristics. Most clinical exploration of immunomodulators focusses on enhancing T-cell mediated anti-tumour immunity but our data suggest that synergistic combination of a tumour checkpoint controller and immunostimulation can be appropriate for poorly immunogenic GBM that is refractory to T-cell control. Legal entity responsible for the study: The authors. Funding: Basilea Pharmaceutica Ltd. Disclosure: P. McSheehy: Shareholder / Stockholder / Stock options, Full / Part-time employment: Basilea Pharmaceutica Ltd.. F. Bachmann: Shareholder / Stockholder / Stock options, Full / Part-time employment: Basilea Pharmaceutica Ltd.. H. Lane: Shareholder / Stockholder / Stock options, Full / Part-time employment: Basilea Pharmaceutica Ltd.. P.R. Walker: Advisory / Consultancy, Research grant / Funding (self): Basilea Pharmaceutica Int. Ltdtd. All other authors have declared no conflicts of interest.